Optimierung der Energieeffizienz zweibeiniger Roboter durch elastische Kopplungen - Bauer, Fabian (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2014)
This work investigates the optimization of bipedal robots’ energy efficiency by using elastic couplings. The regarded robots are modeled as underactuated systems and controlled by input-output linearization. To investigate the influence of elastic couplings on energy efficiency as well as stability and robustness the movements of the robots as well as their elastic couplings are simultaneously optimized using numerical algorithms.